2022
DOI: 10.3390/su14095022
|View full text |Cite
|
Sign up to set email alerts
|

Steel Slag and Recycled Concrete Aggregates: Replacing Quarries to Supply Sustainable Materials for the Asphalt Paving Industry

Abstract: Various researchers are developing efforts to integrate waste and by-products as alternative materials in road construction and maintenance, reducing environmental impacts and promoting a circular economy. Among the alternative materials that several authors have studied regarding their use as partial or total substitutes for natural aggregates in the asphalt paving industry, the steel slag aggregate (SSA) and recycled concrete aggregate (RCA) from construction demolition waste (CDW) stand out. This paper revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 155 publications
0
5
0
Order By: Relevance
“…Reusing steel helps conserve natural resources and reduces associated extraction and manufacturing costs by reducing the reliance on virgin materials. This, in turn, contributes to the overall economic efficiency of road construction projects [56].…”
Section: The Economic and Environmental Impact Of Reused Steel In Roa...mentioning
confidence: 99%
“…Reusing steel helps conserve natural resources and reduces associated extraction and manufacturing costs by reducing the reliance on virgin materials. This, in turn, contributes to the overall economic efficiency of road construction projects [56].…”
Section: The Economic and Environmental Impact Of Reused Steel In Roa...mentioning
confidence: 99%
“…In a review paper [8], the authors concluded that several properties of steel slag aggregates (e.g., roughness, shape, angularity, hardness, polishing resistance, and wear resistance) make them suitable for use in asphalt mixtures. In brief, the SSAs have a low presence of fines, a high sand equivalent, a good shape with high angularity, rough texture, a high density (3.2-3.8 g/cm 3 ), and high porosity and water absorption [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Addressing quarry waste disposal is crucial to the ecological restoration of quarry areas 8,9 . Quarry waste serves as a raw material in the production of concrete and ceramic tiles, and as a construction material for highways 10 . However, most research primarily concentrates on ne particles smaller than 4-5 mm, with limited studies addressing coarsegrained slag 11,12 .This coarse slag possesses a loose structure, with particles typically in point contact.…”
Section: Introductionmentioning
confidence: 99%